Polarography of Walker tumor submitted to radiotherapy. - Sakate, M. [UNESP]; Vercesi, L. [UNESP]; Henry, M. A. [UNESP]; Lucchiari, P. H. [UNESP] (SAGE Publications, 1987)
A polarographic study of oxygen was done in 57 rats inoculated with Walker 256 tumor and platinum electrode implanted in muscle and in tumor. The goal of the research was the study of oxygen in tumor before and after irradiation. Tumor growth caused a decrease in tumoral oxygen. Oxygen was always lower in the tumor than in the muscle. Radiotherapy with 2000 rad (but not with 1000 rad) increased oxygen in the tumor.